The two-spotted spider mite Tetranychus urticae Koch and the carmine spider mite Tetranychus cinnabarinus (Boisduval) in China mixed in their Wolbachia phylogenetic tree - Xie, Lin; Miao, Hui; Hong, Xiao-Yue (Zootaxa, 2006)
Two closely-related species Tetranychus urticae Koch and T. cinnabarinus (Boisduval) are important pests in China causing great damage to agricultural crops. Morphological differentiation between these two spider mite species has been very difficult due to intraspecific variation among populations. Molecular data suggest they are two forms of one species. We approach this problem from a different angle, and attempt to differentiate between the two mites using Wolbachia symbionts, which may show co-evolutionary trends with their hosts. All of the 13 populations of T. urticae from China were found to be infected with Wolbachia, with the infection rate ranging from 2.5% to 85%. Among the 25 populations of T. cinnabarinus examined, seven populations (Shenyang, Yinchuan, Binzhou, Wei’xian, Minhang, Chibi and Gaoxiong) were not infected with Wolbachia, and the other 18 populations were infected, at an infection rate from 5% to 77.5%. No correlation was found between species of host plant and Wolbachia infection rate in either mite. Wolbachia wsp gene sequence analysis showed that there are two clades of Wolbachia from the spider mites. In the Con clade, three Wolbachia strains from T. cinnabarinus (red) in China were mixed with those from two T. urticae (green) populations from France. In Ori clade, two sub-clades were visible. In one sub-clade, fifteen Wolbachia strains from T. cinnabarinus (red) were mixed with eight T. urticae (green; six from China and two from USA and France). In another sub-clade, seven Wolbachia strains from Chinese T. urticae populations (green) were mixed with those from one French red form and five green forms from France, Australia and Japan. Therefore, T. urticae and T. cinnabarinus from China are mixed in the phylogenetic tree of their endosymbiont Wolbachia.